Impact of muscle mass on survival of patients with hepatocellular carcinoma after liver transplantation beyond the Milan criteria. Issue 5 (10th August 2022) - Beumer, Berend R.; van Vugt, Jeroen L.A.; Sapisochin, Gonzalo; Yoon, Peter; Bongini, Marco; Lu, Di; Xu, Xiao; De Simone, Paolo; Pintore, Lorenzo; Golse, Nicolas; Nowosad, Malgorzata; Bennet, William; et al.
Abstract: Background: Access to the liver transplant waitlist for patients with hepatocellular carcinoma (HCC) depends on tumour presentation, biology, and response to treatments. The Milan Criteria (MC) represent the benchmark for expanded criteria that incorporate additional prognostic factors. The purpose of this study was to determine the added value of skeletal muscle index (SMI) in HCC patients beyond the MC. Method: Patients with HCC that were transplanted beyond the MC were included in this retrospective multicentre study. SMI was quantified using the Computed Tomography (CT) within 3 months prior to transplantation. Cox regression models were used to identify predictors of overall survival (OS). The discriminative performance of SMI extended Metroticket 2.0 and AFP models was also assessed. Results: Out of 889 patients transplanted outside the MC, 528 had a CT scan within 3 months prior to liver transplantation (LT), of whom 176 (33%) were classified as sarcopenic. The median time between assessment of the SMI and LT was 1.8 months (IQR: 0.77–2.67). The median follow‐up period was 5.1 95% CI [4.7–5.5] years, with a total of 177 recorded deaths from any cause. In a linear regression model with SMI as the dependent variable, only male gender (8.55 95% CI [6.51–10.59], P  < 0.001) and body mass index (0.74 95% CI [0.59–0.89], P  < 0.001) were significant. Univariable survival analysis of patients with sarcopenia versus patients without sarcopenia showed a significant difference in OS (HR 1.44 95% CI [1.07 − 1.94], P  = 0.018). Also the SMI was significant (HR 0.98 95% CI [0.96–0.99], P  = 0.014). The survival difference between the lowest SMI quartile versus the highest SMI quartile was significant (log‐rank: P  = 0.005) with 5 year OS of 57% and 71%, respectively. Data from 423 patients, describing 139 deaths, was used for multivariate analysis. Both sarcopenia (HR 1.45 95% CI [1.02 − 2.05], P  = 0.036) and SMI were (HR 0.98 95% CI [0.95–0.99], P  = 0.035) significant. On the survival scale this translates to a 5 year OS difference of 11% between sarcopenia and no sarcopenia. Whereas for SMI, this translates to a survival difference of 8% between first and third quartiles for both genders. Conclusions: Overall, we can conclude that higher muscle mass contributes to a better long‐term survival. However, for individual patients, low muscle mass should not be considered an absolute contra‐indication for LT as its discriminatory performance was limited.